Sulphate and sulphurous acid alter the relative susceptibility of wheat to Phaeosphaeria nodorum and Mycosphaerella graminicola. (12th March 2013) - Chandramohan, P.; Shaw, M. W.
Abstract : The relative abundances of DNA of Mycosphaerella graminicola and Phaeosphaeria nodorum in archived wheat samples are closely correlated with UK anthropogenic emissions of oxidized sulphur over the last 160 years. To test whether this could be a causal relationship, possible modes of action of sulphur on the two fungi were examined. Mycelial growth of the two fungi in solutions of sulphurous acid was similar. Sulphurous acid at pH 4 reduced percentage germination of P. nodorum conidia more strongly than M. graminicola conidia. In spray inoculations of wheat cv. Squarehead's Master, Cappelle Desprez and Riband with water or sulphurous acid (pH 4), the ratio of leaves infected by P. nodorum to leaves infected by M. graminicola was increased by factors of 2·5, 2·1 and 0·6, respectively at pH 4. The same three cultivars of wheat were grown in sand and vermiculite and fertilized with nutrient solution containing 2·5 or 0·5 mm sulphate. Both pathogens infected less frequently at 2·5 mm sulphate, by a factor of about 2. The severity of infection by M. graminicola was reduced on all three cultivars by a factor of about 4·5 at 2·5 mm sulphate, but severity of P. nodorum was reduced only by a factor of about 2. Both elevated free sulphate concentrations in soil and sulphite in rainwater could therefore increase the prevalence of P. nodorum relative to M. graminicola, which is consistent with the historical changes in abundance.